2017
DOI: 10.1016/j.hlc.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A Small Cohort Omega-3 PUFA Supplement Study: Implications of Stratifying According to Lipid Membrane Incorporation in Cardiac Surgical Patients

Abstract: This small n-3 PUFA case study demonstrates that the same cohort may yield differing findings when evaluated using randomisation or stratification approaches based on direct molecular measures in cell membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research has shown that n-3 PUFAs have indispensable physiological and health functions in the body [ 11 ]. They have been shown to have special preventive effects on cancer [ 12 ], cardiovascular diseases [ 13 , 14 ] and neurological diseases [ 15 ] in a variety of animal models. According to report, long-term intake of excessive n-6 polyunsaturated fatty acids may increase the possibility of breast cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that n-3 PUFAs have indispensable physiological and health functions in the body [ 11 ]. They have been shown to have special preventive effects on cancer [ 12 ], cardiovascular diseases [ 13 , 14 ] and neurological diseases [ 15 ] in a variety of animal models. According to report, long-term intake of excessive n-6 polyunsaturated fatty acids may increase the possibility of breast cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%